Pengaruh gratitude terhadap kepuasan pernikahan - Novianty, Sherla; Aditya, Yonathan (Konsorsium Psikologi Ilmiah Nusantara, 2013)
Gratitude is known to improve ability to cope with stress and to increase well-being. This research was conducted in order to study the effect of gratitude on marital satisfaction: both on actor and partner. This research used The Gratitude Questionnaire-Six-Item Form (GQ-6) and Relationship Assessment Scale (RAS). The respondent of this study was 180 couples who live in Jakarta. This study found that husbands’ gratitude has a signiicant effect on husbands’marital satisfaction (β = .31, p = 0.0), and on wives’ marital satisfaction (β = .48, p = 0.0). The same was also true on wives’ gratitude. Wives’ gratitude has a signiicant effect on wives’ marital satisfaction (β = .58, p = 0.0), and husbands’ marital satisfaction (β = .20, p = .004).